Aluminum nitride–filled elastic silicone rubber composites for drag reduction. (April 2017) - Tian, Limei; Wang, Yangjun; Jin, E; Li, Yinwu; Wang, Runmao; Shang, Yangeng
This study presents aluminum nitride/silicone rubber composite as a drag reduction material, inspired by the boundary heating drag reduction mechanism of dolphin skin. Aluminum nitride was added as a thermal conductive filler at weight fractions of 16.67, 21.05, and 28.57 wt% to pristine silicone rubber. Tests of the thermal conductivity and tensile properties showed that the thermal conductivity of all three aluminum nitride/silicone rubber composites were increased 27.9%, 41.4%, and 43.7% than that of the pristine silicone rubber, and the elastic modulus of the composites was increased with the aluminum nitride content. Droplet velocity testing, which can reflect the drag reduction mechanism of the heating boundary controlled by the aluminum nitride/silicone rubber composites, was performed between all three aluminum nitride/silicone rubber composites and pristine silicone rubber. The results showed that the droplet velocity of all three aluminum nitride/silicone rubber composites were higher than pristine silicone rubber, implying that the composites had a drag-reducing function. In terms of the drag-reducing mechanism, the heat conductivity performance of the aluminum nitride/silicone rubber accelerates the heat transfer between the aluminum nitride/silicone rubber composite surface and droplet. The forces between the molecules and droplet dynamic viscosity are reduced, which result in drag reduction. The application of aluminum nitride/silicone rubber composite to control fluid medium will have important value for fluid machinery.